Effects of Thiourea on the Corrosion of Low Carbon Steel in Hydrochloric Acid Solution - SuUiman, I. D. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The c.orrosion rate of  low carbon  steel  in 4M  hydrochlwic acid with and without  presence of thiourea has b.een studied  by gravimetric ahd gasometric methods  over the temperature range 303-333 K. The percentage protection of steel increases  vvith the decrease of thimuea concentrations at  various  temperature range  303-333 K andapproaching highest  protection  (86.82%) at 303K  by using  I X 1 o-4 Mof thiourea. The high concentration .of thiourea  ( lxlo-3 M), enl1ances.the  corrosion rates and  act  as dcpolariser for  the hydrogen  evolutionreaction,  with  H2S bei11g a  product   of  the  chemical   depolarisation â€¢ stage.  The  ff2S  is  considered  to  be adsoJ'bed  in the  s-2 HS-  state, forming  activated sites where anodic dissolution is thereby enhanced. The result's wetÂ·e discussed on basis of adsorption of dissociated thiourea  molecules on  steel  .surface.  The  energies of  activation have been  calculated for  the corrosiOn  process  of  the carbon  steel  in acid from corrosion rates in: tbeabsenee and the presence of thiourea.